2017
DOI: 10.1002/2016jd025817
|View full text |Cite
|
Sign up to set email alerts
|

Ice cloud formation potential by free tropospheric particles from long‐range transport over the Northern Atlantic Ocean

Abstract: Long‐range transported free tropospheric particles can play a significant role on heterogeneous ice nucleation. Using optical and electron microscopy we examine the physicochemical characteristics of ice nucleating particles (INPs). Particles were collected on substrates from the free troposphere at the remote Pico Mountain Observatory in the Azores Islands, after long‐range transport and aging over the Atlantic Ocean. We investigate four specific events to study the ice formation potential by the collected pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
116
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(139 citation statements)
references
References 113 publications
(195 reference statements)
22
116
1
Order By: Relevance
“…This study also suggests that dust particles coated with organic particles, which are observed within~75% of the ambient particles (Figure 4) can nucleate ice (see experiment A results; Figure 5) at water saturation conditions, These findings are consistent with many previous studies which investigated the ice nucleation ability of pure and organic-coated particles [58][59][60][61]. For example, Tobo et al (2012) [59] observed that at water-saturated conditions only sulfuric acid-coated kaolinite particles showed a reduction in ice nucleation efficiency and that the results were unaffected when these particles were coated with levoglucosan, a water-soluble organic compound.…”
Section: Inp Measurementssupporting
confidence: 91%
“…This study also suggests that dust particles coated with organic particles, which are observed within~75% of the ambient particles (Figure 4) can nucleate ice (see experiment A results; Figure 5) at water saturation conditions, These findings are consistent with many previous studies which investigated the ice nucleation ability of pure and organic-coated particles [58][59][60][61]. For example, Tobo et al (2012) [59] observed that at water-saturated conditions only sulfuric acid-coated kaolinite particles showed a reduction in ice nucleation efficiency and that the results were unaffected when these particles were coated with levoglucosan, a water-soluble organic compound.…”
Section: Inp Measurementssupporting
confidence: 91%
“…Furthermore, it is possible that aging processes may not affect the ice nucleation ability of ambient particles given that the range of n s during FT background is similar to that of the BLI as seen in Figure 4. In a study by China et al (2017), a very small change in the ice nucleation activity between ambient particles was observed, despite differences in the particle chemical composition, source regions, and transport pathways. They concluded that aging did not play a significant role in the ice nucleation activity of ambient particles.…”
Section: Classification Of Inp Concentrationsmentioning
confidence: 95%
“…However, the increased concentration of methane sulfonic acid (MSA) in PMO-2 relative to PMO-1 and PMO-3 suggests some degree of marine influence. To estimate this, we used the non-background subtracted sodium concentration as an upper limit to estimate sea salt sulfate according to the method described in Chow et al (2015), this led to a maximum sea salt sulfate contribution of 25 %. The influence of marine sources supports boundary layer transport.…”
Section: Flexpart Numerical Simulationsmentioning
confidence: 99%